Enhancing the Value of Sweet Potatoes in Madagascar: Between Food Security and Productive Capital – A Socio-Anthropological Approach - Ramangarijaona Simon Ludovic; Raherimalala Etienne Stefano; Ravelo Bruno Eugène Maxime; Rakotorahalahy Njaka Herihajatsilaozana Elisabeth; Ravelonjatovo Haja Herilala; Andrianjary Myriam; Ratiarimananjatovo Narindra; Robijaona Rahelivololoniaina Baholy (Britain International of Exact Sciences (BIoEx) Journal, 2025)
This study focuses on the valorization of sweet potatoes in Madagascar from the perspective of food security and the accumulation of productive capital, as defined by Nurkse—that is, through the establishment of basic infrastructure. The research was conducted in the geographic areas of Ankazobe, in the northern highlands, as well as in Tsarasaotra in the Amoron'i Mania region, and in Soaindrana and Talata Ampano in the Matsiatra Ambony region. These areas are distinguished by their diverse sociocultural and economic characteristics. The central question is whether it is reasonable to consider development based on a modest, indigenous yet widespread resource like the sweet potato. The findings indicate that if its production were to increase, following a shift in the devaluing perceptions commonly associated with it, this would lead to strengthened food security. Furthermore, if basic innovations—both technical and organizational—are adopted in rural settings, the production of this tuber crop could promote the rapid accumulation of productive capital, a key element in any development process. Drawing on De Sardan’s framework of entangled social logics, which emphasizes changes in mentality, the concept of agency, and Weber’s ideal-type vision of capitalism, the objective is to move away from grand macroeconomic development theories and adopt a pragmatic approach centered on local potential. Development must therefore be rethought as a cultural process, grounded in representations and enculturated behaviors (habitus, hexis), by establishing a link between increased production and rural mentalities. The study also shows that ongoing innovations in production methods—such as those related to sweet potatoes—do not necessarily need to be expensive to trigger mechanisms for the formation of productive capital.